2015
DOI: 10.21276/ambi.2015.02.1.ra02
|View full text |Cite
|
Sign up to set email alerts
|

Food Habits of Spotted Owlet Athene brama (Temminck, 1821) in the Campus of Tropical Forest Research Institute, Jabalpur: an Ecological representation of Central India

Abstract: by analyzing their regurgitated pellets. The insect order Coleoptera with three dung beetle species, and two orders and f ive species of small mammals, and were recorded from the pellets. The other insect taxa found in the pellets include Carabidae and Hydrophilidae beetles and Earwigs in the order Dermaptera. This is for the f irst time food habits of the spotted owlets, being reported from the state of Madhya Pradesh, which further provides identifying key characters of the dung beetles along with illustrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…In present study, insects alone constituted 53.8% and small mammals constituted 45% of the diet of Spotted Owlet. Paunikar et al (2015) studied the food habits of the Spotted Owlet in Tropical Forest Research Institute campus, Jabalpur, India by analyzing their regurgitated pellets and found the remains of three dung beetle species, Onitis philemon, Onitis virens and Onitis brahma and five species of small mammals, M. booduga, Vandeleuria oleracea, M. meltada, Suncus etruscus and Suncus murinus. In the present study, however, the diet of Spotted Owlet was found constituted only of M. booduga among small mammals, particularly the rodents.…”
Section: Food Consumptionmentioning
confidence: 99%
“…In present study, insects alone constituted 53.8% and small mammals constituted 45% of the diet of Spotted Owlet. Paunikar et al (2015) studied the food habits of the Spotted Owlet in Tropical Forest Research Institute campus, Jabalpur, India by analyzing their regurgitated pellets and found the remains of three dung beetle species, Onitis philemon, Onitis virens and Onitis brahma and five species of small mammals, M. booduga, Vandeleuria oleracea, M. meltada, Suncus etruscus and Suncus murinus. In the present study, however, the diet of Spotted Owlet was found constituted only of M. booduga among small mammals, particularly the rodents.…”
Section: Food Consumptionmentioning
confidence: 99%